Risālah-yi inʻāmulbārī fī sharḥ ashʻārulbuḵẖārī - Ilāhī, Muḥammad ʻĀshiq (Maktabah-yi Dārulʻulūm ; milne ke pate, Maktabah-yi Imdādiyyah, 1978)
Explanatory notes on the Arabic verses quoted in Ṣaḥīḥ al-Bukhārī, a compilation of Hadith (Islamic traditions) by Muḥammad ibn Ismāʻīl al-Bukhārī, 810-870.